The Effect Of Capital Structure On Profitability In The Registered Financial Services Industry On The Indonesian Stock Exchange (Bei) - Nur Rahma; Asriani Hasan; Ismawati, Ismawati (CV. AFDIFAL MAJU BERKAH, 2024)
Capital structure is an important issue that companies must pay attention to because capital structure is expected to increase profitability, which is the goal of every company. This research aims to determine the effect of capital structure on profitability in financial services industry companies listed on the Indonesia Stock Exchange (BEI). This research uses quantitative methods with explanatory research. The sampling technique in this research is purposive sampling. The data analysis technique in this research uses multiple linear regression analysis. The results of this research show that capital structure as measured by the Debt to Asset Ratio (DAR) has a significant positive effect on profitability (Return On Assets) and the Debt to Equity Ratio (DER) has a significant negative effect on profitability (Return On Assets)